X-ray absorption spectroscopy by full-field X-ray microscopy of a thin graphite flake: Imaging and electronic structure via the carbon K-edge - Bittencourt, Carla; Hitchock, Adam P.; Ke, Xiaoxing; Van Tendeloo, Gustaaf; Ewels, Chris P.; Guttmann, Peter (Beilstein Journal of Nanotechnology, 2012)
We demonstrate that near-edge X-ray-absorption fine-structure spectra combined with full-field transmission X-ray microscopy can be used to study the electronic structure of graphite flakes consisting of a few graphene layers. The flake was produced by exfoliation using sodium cholate and then isolated by means of density-gradient ultracentrifugation. An image sequence around the carbon K-edge, analyzed by using reference spectra for the in-plane and out-of-plane regions of the sample, is used to map and spectrally characterize the flat and folded regions of the flake. Additional spectral features in both π and σ regions are observed, which may be related to the presence of topological defects. Doping by metal impurities that were present in the original exfoliated graphite is indicated by the presence of a pre-edge signal at 284.2 eV.
Keywords: carbon; graphene; nanostructure; NEXAFS; X-ray microscopy

(untitled) - Gan, Y.; Sun, L.; Banhart, F. (Small, 2008)

(untitled) - Blake, P.; Hill, E. W.; Castro Neto, A. H.; Novoselov, K. S.; Jiang, D.; Yang, R.; Booth, T. J.; Geim, A. K. (Appl. Phys. Lett., 2007)

(untitled) - Castro Neto, A. H.; Guinea, F.; Peres, N. M. R.; Novoselov, K. S.; Geim, A. K. (Rev. Mod. Phys., 2009)

(untitled) - Boehm, H.-P. (Angew. Chem., Int. Ed., 2010)

(untitled) - Chuvilin, A.; Kaiser, U.; Bichoutskaia, E.; Besley, N. A.; Khlobystov, A. N. (Nat. Chem., 2010)

(untitled) - Lopes, P. L. e S.; Castro Neto, A. H.; Caldeira, A. O. (Phys. Rev. B: Condens. Matter Mater. Phys., 2011)

(untitled) - Krasheninnikov, A. V.; Nieminen, R. M. (Theor. Chem. Acc., 2011)

(untitled) - Lehtinen, O.; Kotakoski, J.; Krasheninnikov, A. V.; Keinonen, J. (Nanotechnology, 2011)

(untitled) - Cançado, L. G.; Jorio, A.; Martins Ferreira, E. H.; Stavale, F.; Achete, C. A.; Capaz, R. B.; Moutinho, M. V. O.; Lombardo, A.; Kulmala, T. S.; Ferrari, A. C. (Nano Lett., 2011)

(untitled) - Krstić, V.; Obergfell, D.; Hansel, S.; Rikken, G. L. J. A.; Blokland, J. H.; Ferreira, M. S.; Roth, S. (Nano Lett., 2008)

(untitled) - Stankovich, S.; Dikin, D. A.; Dommett, G. H. B.; Kohlhaas, K. M.; Zimney, E. J.; Stach, E. A.; Piner, R. D.; Nguyen, S. T.; Ruoff, R. S. (Nature, 2006)

(untitled) - Schultz, B. J.; Patridge, C. J.; Lee, V.; Jaye, C.; Lysaght, P. S.; Smith, C.; Barnett, J.; Fischer, D. A.; Prendergast, D.; Banerjee, S. (Nat. Commun., 2011)

(untitled) - Suarez-Martinez, I.; Grobert, N.; Ewels, C. P. (Carbon, 2012)

(untitled) - Papagno, M.; Rodríguez, A. F.; Girit, Ç. Ö.; Meyer, J. C.; Zettl, A.; Pacilé, D. (Chem. Phys. Lett., 2009)

NEXAFS spectroscopy - Stöhr, J. (Springer-Verlag, 2003)

(untitled) - Felten, A.; Gillon, X.; Gulas, M.; Pireaux, J.-J.; Ke, X.; Van Tendeloo, G.; Bittencourt, C.; Najafi, E.; Hitchcock, A. P. (ACS Nano, 2010)

(untitled) - Najafi, E.; Hernández Cruz, D.; Obst, M.; Hitchcock, A. P.; Felten, A.; Douhard, B.; Pireaux, J.-J.; Kaznatcheev, K.; Karunakaran, C. (J. Phys.: Conf. Ser., 2009)

(untitled) - Felten, A.; Bittencourt, C.; Pireaux, J.-J.; Reichelt, M.; Mayer, J.; Hernandez-Cruz, D.; Hitchcock, A. P. (Nano Lett., 2007)

(untitled) - Guttmann, P.; Bittencourt, C.; Rehbein, S.; Umek, P.; Ke, X.; Van Tendeloo, G.; Ewels, C. P.; Schneider, G. (Nat. Photonics, 2011)

NanoIntegris

(untitled) - Green, A. A.; Hersam, M. C. (Nano Lett., 2009)

(untitled) - Brownson, D. A. C.; Metters, J. P.; Kampouris, D. K.; Banks, C. E. (Electroanalysis, 2011)

(untitled) - Zeng, X.; Duewer, F.; Feser, M.; Huang, C.; Lyon, A.; Tkachuk, A.; Yun, W. (Appl. Opt., 2008)

(untitled) - Najafi, E.; Hernández Cruz, D.; Obst, M.; Hitchcock, A. P.; Douhard, B.; Pireaux, J.-J.; Felten, A. (Small, 2008)

(untitled) - Li, Z.; Zheng, L.; Yan, W.; Pan, Z.; Wei, S. (ChemPhysChem, 2009)

(untitled) - Hua, W.; Gao, B.; Li, S.; Ågren, H.; Luo, Y. (Phys. Rev. B, 2010)